2016
DOI: 10.4103/0301-4738.181740
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of success after second Ahmed glaucoma valve implantation

Abstract: Purpose:To evaluate the outcome of the second Ahmed glaucoma valve (AGV) surgery in eyes with failed previous AGV surgery.Design:Retrospective case series.Patients and Methods:Following chart review, 36 eyes of 34 patients with second AGV implantation were enrolled in this study. The primary outcome measure was surgical success defined in terms of intraocular pressure (IOP) control using two criteria: Success was defined as IOP ≤21 mmHg (criterion 1) and IOP ≤16 mmHg (criterion 2), with at least 20% reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…For these reasons, in both centers, devices with flow-restricting technology have been preferred. In terms of efficacy, our results are in line with those already published in the literature [19][20][21][22][23][24][25][26][27][28]. The success rate reported in a recent metanalysis of Yoon et al [29] ranged between 37% to 83% at three years with a significant reduction in glaucoma medications.…”
Section: Discussionsupporting
confidence: 90%
“…For these reasons, in both centers, devices with flow-restricting technology have been preferred. In terms of efficacy, our results are in line with those already published in the literature [19][20][21][22][23][24][25][26][27][28]. The success rate reported in a recent metanalysis of Yoon et al [29] ranged between 37% to 83% at three years with a significant reduction in glaucoma medications.…”
Section: Discussionsupporting
confidence: 90%
“…ese studies were not carried out in Asian countries, with the exception of one, Ko et al in Korea. ey reported similar success rates ranging from 62.9% to 87.0% at one year, 56.6% to 80.0% at two years, and 52.0% to 57.0% at three years of follow-up [16][17][18][19][20]. e study on Asian eyes by Ko et al showed very similar success rates to our results.…”
Section: Discussionsupporting
confidence: 87%
“…Our study showed higher success rates at all three intervals compared to that of Jiménez-Román et al, possibly due to the high proportion of S2 polypropylene models as the second AGV in their study; polypropylene models have been reported to have poorer survival estimates than the silicone models [19,21]. e success rates of the second AGV at the last follow-up in these studies ranged from 65.2% (Ko et al) to 84.2% (Smith et al), while our study had a lower success rate of 57.1% at the last follow-up [16][17][18]. is could be attributed to a longer mean follow-up time of 49.2 months in our study as compared to the studies evaluated (range: 21.4 months-37.8 months), which led to a greater proportion of AGV failure over time.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations